HUBUNGAN DINAMIKA KELOMPOK DENGAN PRODUKTIVITAS PETERNAK DOMBA DI PAGUYUBAN AL-AWWALIYAH, PASIR WANGI, GARUT - Inayatullah I; Ujang Maman; Iwan Aminudin (AGRIBUSINESS JOURNAL, 2018)
This study aims to find out how the group dynamic conditions, the productivity of farmers, and the relationship between group dynamics and productivities of breeders KTN assisted in Al-Awwaliyah Community, Garut, West Java. The Spearman Rank was employed to analyze the data. Rank Spearman statistical test results showed that the purpose of the group, the group structure, the function of the task group, the development and the maintenance of the group, the group atmosphere, and the peer pressure associated with the productivity of breeders. Of the six indicators of group dynamics, group environment indicators occupy the highest ratings in the amount of 95.6 %. Besides, of the three indicators of the productivity of breeders, high confidence indicators occupy the highest ratings in the amount of 84.4 %.